A Study on Performance of Mandarin Speaking Test among Non-Native Speakers through Bio-Feedback - Yong, Ying Mei; Sharifah Intan Safina, Syed Zubir; Muhammad Nubli, Abdul Wahab (Medwell Journals, 2018)
The advantages of mastering Mandarin as a Foreign language may increase competence among students in working fields in future, especially those who are able to communicate in Mandarin well. In Universiti Malaysia Pahang (UMP), the number of students enrolling in Mandarin course is increasing every year. However, some students demonstrate good performance in Mandarin speaking test while some students are weak. This study investigated the student’s performance in Mandarin speaking test between good performers and weak performers through bio-feedback, specifically Heart Rate Variability (HRV). A total of 86 non-Chinese students from Mandarin for intermediate course took part as the respondents. A total of 30 out of the 86 students were chosen as focus group. The research instruments included Mandarin speaking script, bio-feedback instrument and Mandarin speaking test evaluation form. The frequency analysis by HRV aimed to investigate the level of stress and relax on Mandarin speaking test among focus group students. The finding shows the comparison of the performance of the Mandarin speaking test between good performers and weak performers through HRV. From this study, it can be concluded that positives stress will motivate students to perform well while too relax can cause student’s performance weak in Mandarin speaking test. Therefore, the balance of stressful and relax by controlling emotion can influence to student’s performance in Mandarin speaking test.